2015
DOI: 10.1159/000369206
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Chronic Hepatitis C Patients Treated with Interferon-Alpha: Risk of Cirrhosis and Hepatocellular Carcinoma in a Single Center over 10 Years

Abstract: Objectives: Interferon (IFN)-based therapy for chronic hepatitis C (CHC) is cost-effective and is associated with reduced risk of disease progression. We aimed to assess the incidence of cirrhosis and hepatocellular carcinoma (HCC) and to identify risk factors associated with disease progression. Methods: We retrospectively reviewed 280 CHC patients who were registered at our hospital between 2001 and 2010. Results: About 80% of patients received antiviral treatment. The 10-year cumulative incidence of cirrhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The increase in the incidence of cirrhosis may be explained by the fact that the vast majority of our patients (96%) were infected with the more aggressive genotype (genotype 1). Annual rate of cirrhosis was found to be 2.26-5% in previous studies for the untreated patients [8,9] , which was similar to our results (4.44%). The annual rate of cirrhosis (1.95%) was significantly declined in treated group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in the incidence of cirrhosis may be explained by the fact that the vast majority of our patients (96%) were infected with the more aggressive genotype (genotype 1). Annual rate of cirrhosis was found to be 2.26-5% in previous studies for the untreated patients [8,9] , which was similar to our results (4.44%). The annual rate of cirrhosis (1.95%) was significantly declined in treated group.…”
Section: Discussionsupporting
confidence: 93%
“…C. Koh et al [14] and Morisco F et al [15] also showed that CHC patients with SVR has a markedly reduced risk for relapse and cirrhosis (0.97%, 0.77 respectively). Lee HJ et al [8] followed up 280 CHC patients for 10 years in Korea and the cumulative incidences of cirrhosis were found to be 0.6% in patients with SVR, 33.9% in patients without SVR and 44.4% in untreated group. In this study, similar results were observed as treated patients without SVR had lower cirrhosis incidence comparing to untreated patients, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…2008 [ 64 ] Japan 209 4.1 years a Retrospective cohort study in patients who underwent curative surgery for early stage HCC (n = 139 had no antiviral treatment, remainder treated with pegIFN plus ribavirin) Tumor-free survival and recurrence of HCC Tumor-free survival rate at 5 years was 54% for SVR group vs. 23% for non-SVR/untreated group (p < 0.001) Lee et al . 2013 [ 80 ] South Korea 315 45 months a Retrospective chart review, 86% patients treated, 15% with cirrhosis at baseline, SVR rate of 75% Cirrhosis Cumulative 5 year rate of cirrhosis was 27.6% for patients without SVR vs. 0% for patients with SVR (p < 0.01) Canete et al . 2013 [ 81 ] Spain 105 9.3 years Retrospective study of paired biopsy data in HCV patients with mild-moderate fibrosis treated with IFN plus ribavirin Progression of fibrosis Progression of fibrosis was reported in 5.3% patients with SVR and 50% patients with non-response (p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%